"SCREAMING IN DELIGHT": qiu miaojin's queer modernist births in and for taiwan1. Issue 3 (4th July 2022) - Acadia, L.
Abstract: Introspective crocodiles and exhibitionist writers, queered gender and temporality, critiques of capitalism and canon, experimental form and technique, speculative storylines traversing the cityscape, and physical if unconsummated young love characterize Qiu Miaojin's distinctive novel, Notes of a Crocodile . A foundational work of Taiwanese queer literature whose protagonist's name became the word for "lesbian" across the Mandarin-speaking world, the novel captures the queer experience at the moment of birth for a new country, while looking to the future. Bittersweet juxtapositions of pain and pleasure in the protagonist's relationships with characters, countries, and concepts show how, struggling with complex inner worlds, Qiu births a queer world.